ZAMONAVIY INGLIZ TILIDA PRAGMATIKA VA SO'Z MA'NOSI (Universal xalqaro ilmiy jurnal, 2026)
n this article it will explore the relationship between pragmatics and word meaningwith a focus on Modern English, and how meaning is influenced not only by grammatical form, but alsoby context, speaker intention, and social interaction. Whereas traditional semantics considers meaningas a stable property of words and sentences, pragmatics emphasizes that meaning is negotiated in actualcommunicative contexts. The paper takes as its goal to provide a close analysis of such critical pragmaticconcepts as context, deixis, implicature, presupposition, and speech acts, showing how those ideasinfluence the interpretation of lexical meaning in everyday communication.One point of particular focus with which he brings attention is that of dynamic word meanings inmodern English—most especially in digital discourse, media, and intercultural communication. Thestudy shows that understanding word meaning demands not just dictionary definitions but anunderstanding also of norms and attitudes in society, one's cultural background, and of communicativeaims—often based upon examples from actual usage.The relative importance of pragmatics in explaining implicit meanings of speakers, and howlisteners interpret them successfully. In an attempt to establish a conclusion, the article argues thatpragmatics is a defining factor and is relevant in modern English through word meanings; pragmatics isone of the major theories in both modernism and modern Western English which is needed for efficientcommunication, linguistic analysis etc
Keywords: pragmatika; so'z ma'nosi; zamonaviy ingliz tili